Design and implementation a security system for bank using voice recognition - Ali, Mohammed Hasan; Al Azze, Qasim mohamed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
In this work, a new security system design is demonstrated based on the sound signal for bank protection. Voice Acknowledgment Module is placed on the gate of the safe. Voice Acknowledgment Module is set to perceive the capable client as indicated by his sound recurrence reaction. The plan could program to permit tow clients for greater adaptability the card location strategy is executed utilizing individual data information to permit other client in the framework. A delicate camera is accustomed to observing the developments in the structure and for the reasons for wellbeing and security. All these sensors are controlled by arduino.